Comparison between INTERGROWTH-21ST and Fenton charts for extrauterine growth in very low birth weigth infants - Ilkyaz Turktan; Omer Erdeve; Ezgi Kostekci; Emel Okulu; Begum Atasay; Saadet Arsan (Italian Journal of Pediatrics)
Abstract Background The growth of premature infants is expected to be equivalent to healthy fetal growth, but this is rarely achieved in practice. It is predicted that many premature infants, especially severe premature infants, will be discharged with growth restriction. Extrauterine growth retardation (EUGR) is defined as growth below the 10th percentile of the growth curve at discharge at corrected 36th/40th week of gestation, or a difference between birth and discharge z-score > 1 SD. The aim of our study is to determine the differences between the INTERGROWTH-21ST and the Fenton chart in the assessment of extrauterine growth. Methods Infants < 1500 g born or transferred in the first 24 h at Ankara University NICU between January 1, 2015 and December 31, 2019 were included. Infants with major congenital anomalies, unknown gestational age, chromosomal anomalies, hydrops fetalis, TORCH infection, infants born to substance abusing mothers, and infants who died during hospitalization were excluded. Results According to the Fenton, the rate of EUGR at discharge was 66.3%. There was no significant difference between the groups EUGR and non-EUGR in gender, gestational diabetes, maternal smoking during pregnancy, placental abruption, magnesium sulphate prophylaxis, development of respiratory distress, and need for intubation in the first 3 days after birth. When patients were grouped according to birth weight, the highest rate of EUGR according to the Fenton was found in the group with a birth weight ≤ 1000 g (78.8%) (p = 0.036). The proportion of patients defined as SGA by INTERGROWTH-21ST was significantly higher than by Fenton (p < 0.001). Comparing the mean z scores for body weight, height and head circumference at birth and discharge calculated from the Fenton and INTERGROWTH-21 charts, the z scores for body weight and height at birth and discharge were significantly lower in the INTERGROWTH-21 (p < 0.001). Head circumference z-scores at birth and discharge were found to be higher in the Fenton chart than in the INTERGROWTH-21ST (p < 0.001). When EUGR rates were evaluated by body weight in Fenton and INTERGROWTH-21ST, the EUGR rate was found to be higher in Fenton (p < 0.001). Conclusions The results show that when INTERGROWTH-21ST and Fenton are compared, INTERGROWTH-21ST is more sensitive in defining the SGA rate. The Fenton is more sensitive in defining EUGR at discharge. These differences between the charts make it difficult to monitor the growth of premature infants and to follow comorbidities. Therefore, the establishment of ideal growth curves is of great importance both during hospitalization and after discharge of premature infants.